Transgenic Efficiency of FoxN1-targeted Pig Parthenogenetic Embryos - Jae-Hoon Yeo; In-Sul Hwang; Jae Kyung Park; Dae-Jin Kwon; Seoki Im; Eung-Woo Park; Jeong-Woong Lee; Choon-Keun Park; Seongsoo Hwang (The Korean Society of Animal Reproduction and Biotechnology, 2014)
The clustered regularly interspaced short palindromic repeats (CRISPR)/CRISPR associated protein (Cas9) system can be applied to produce transgenic pigs. Therefore, we applied CRISPR/Cas9 system to generate FoxN1-targeted pig parthenogenetic embryos. Using single guided RNA targeted to pig FoxN1 genes was injected into cytoplasm of in vitro matured oocyte before electrical activation. In results, regardless of the concentrations of vector, the cleavage rate were significantly (p<0.05) decreased (4 ng/μl, 51.24%; 8 ng/μl, 40.88%; and 16 ng/μl; 45.22%) compared to no injection group (70.44%). The blastocyst formation rates were also decreased in vector injected 3 groups (4 ng/μl, 7.96%; 8 ng/μl, 6.4%; and 16 ng/μl; 9.04%) compared to no injection group (29.07%). In addition, the blastocyst formation rates between sham injected group (13.51%) and no injection group (29.07%) also showed significant difference (p<0.05). The mutation rates were comparable between groups (4 ng/μl, 18.4%; 8 ng/μl, 12.5%; and 16 ng/μl; 20.0%). The sequencing analysis showed that blastocysts derived from each group were successfully mutated in FoxN1 loci regardless of the vector concentrations. However, the deletion patterns were higher than the patterns of point mutation and insertion regardless of the vector concentrations. In conclusion, we described that cytoplasmic micro- injection of FoxN1-targeted CRISPR/Cas9 vector could efficiently generate transgenic pig parthenogenetic embryos in one-step.